Wireless Network Security Threats and Best Method to Warn - et. al, Dr. J P Patra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Networking technology is now one of the most popular technologies but still, some drawbacks are closely associated with Wireless Networks. In wireless network communication, the data is transferred from one point to another point through radio waves which makes wireless networks weak for attacks. To eliminate threats, understanding said attacks always provides a good ability to defend the wireless network. This research paper will describe the overview of the wireless technology with its drawbacks, Present security and privacy issues, Potential wireless network Security threats (unauthorized access, Active eavesdropping, Man in the Middle Attack, Denial of Service, etc), tools that hackers often use to exploit vulnerabilities in wireless networking (NetStumbler, Kismet, Airsnort, Airsnarf, Airjack, etc) and will propose the best ways to secure Wireless Network.